(untitled) (Applied Biological Research, 2023)
The present study focused on the effect of antimicrobial agents on direct shoot organogenesis in Oxalis corniculata Linn. The antimicrobial agents evaluated were kanamycin, carbendazim, cefotaxime and silver thiosulphate. The nodal explants, collected from 4-week old shoots of field grown O. corniculata plants, were sterilized by 5% (v/v) Tween-20, followed by 70% ethanol. MS medium was supplemented with alone or in combinations of benzyl aminopurine(BAP), kinetin, naphthalene acetic acid (NAA), indole-3-butyric acid and indole 3-acetic acid. Among the antimicrobial agents tested, carbendazim @ 2 mg L-1 along with BAP @ 1 mg L-1 gave maximum shooting response (80%), higher shoot number (7.8) and longer shoots (4.7 cm); whereas kanamycin (40 µM) showed least response on shooting (75%) and shoot number (4.5). Among the auxins tested, NAA @ 2 mg L-1showed maximum rooting response (95%), root number (22.3) and root length (4.4 cm). Rooted shootlets were successfully hardened in sterile soil + vermiculite (1:1) medium and then transferred to the field. Among the antimicrobial agents tested, carbendazim + BAP resulted in best response on shooting while NAA showed maximum rooting response.